2022
DOI: 10.1186/s13052-022-01307-5
|View full text |Cite
|
Sign up to set email alerts
|

The effect of gestational age, low birth weight and parity on birth asphyxia among neonates in sub-Saharan Africa: systematic review and meta-analysis: 2021

Abstract: Background Despite simple and proven cost-effective measures were available to prevent birth asphyxia; studies suggested that there has been limited progress in preventing birth asphyxia even in healthy full-term neonates. In Sub-Saharan Africa, Inconsistency of magnitude of birth asphyxia and its association gestational age, Low birth Weight and Parity among different studies has been observed through time. Objective This study aimed to estimate t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
2
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 47 publications
2
2
0
2
Order By: Relevance
“…Such an approach has been implemented in India and has been shown to be associated with reduced mortality [ 27 ]. Furthermore, our analysis showed that lower gestational age, prematurity, referred mothers, and advanced maternal age were associated with birth asphyxia, while few retrospective studies have shown variable results; the majority of pooling studies were consistent with our findings [ 18 , 28 ].…”
Section: Discussionsupporting
confidence: 88%
“…Such an approach has been implemented in India and has been shown to be associated with reduced mortality [ 27 ]. Furthermore, our analysis showed that lower gestational age, prematurity, referred mothers, and advanced maternal age were associated with birth asphyxia, while few retrospective studies have shown variable results; the majority of pooling studies were consistent with our findings [ 18 , 28 ].…”
Section: Discussionsupporting
confidence: 88%
“…Similarly, our findings show that babies born with low birth weight has four times increased risk of birth asphyxia compared to normal weight babies. This finding is supported by multiple other studies including the ones done in Beijing Obstetrics and Gynecology Hospital and sub Saharan African, [ 31 , 32 ]. The pathophysiology for this is likely similar to that of preterm babies in which the respiratory systems are not fully developed [ 30 ].…”
Section: Discussionsupporting
confidence: 82%
“…Outre, ils connaissent une chute rapide du PH sanguin foetal. Ce qui les expose d'avantage aux problèmes d'asphyxie périnatale, d'adaptation cardiorespiratoire à la naissance, et du décès néonatal précoce [4,21,22,23]. Dans la même logique de réflexion, l'étude de Goodwin et al a confirmé qu'avec un ph sanguin inférieure 7 le foetus est à haut risque de développer des complications organiques.…”
Section: Discussionunclassified
“…Des valeurs basses d'Apgar indiquent une détresse respiratoire sévère et un pronostic défavorable. Dans cette étude, il y'avait une forte signification entre un score d'Apgar inférieur 3 et la survenue de la mortalité, ce qui est homogène avec plusieurs études antérieures [22,28,29]. Casey et al ont mis en évidence un risque accru de décès associé au score d'Apgar bas .…”
Section: Discussionunclassified